HUBUNGAN KONDISI LINGKUNGAN RUMAH PENDUDUK DENGAN KEJADIAN ISPA PADA BALITA DI DESA SP. KELAPING KECAMATAN PEGASING KABUPATEN ACEH TENGAH - Sahadawati, Eby; Surya Darni, Nelviana; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Acute respiratory infections (ARI) are one of the health problems with a fairly high incidence rate in the world. Acute respiratory infections are known as a source of morbidity and mortality of infectious diseases. This type of research is quantitative with a cross sectional research design design.The population in this study is all mothers who have toddlers in Simpang Kelaping village as many as 323 toddlers, the sample size was determined using the slovin formula and a sample of 70 toddlers was obtained and determined by purposive sampling technique. The purpose of this study is to prove the relationship between home environmental conditions and the incidence of ISPA in toddlers in Simpang Kelapa village, Pegasing, Central Aceh. Analysis of the results data used the Chi-Square test with a significant level (p<0.05). The results of the statistical test showed a relationship between house ventilation (p=0.000) (<0.05), natural lighting (p=0.001) (<0.05), humidity (p=0.003) (<0.05), residential density (p=0.008) (<0.05) and the incidence of ISPA. Therefore, it is recommended that respondents always clean the home environment and do not combine the room of the toddler. Keywords : Home Environment, Acute Respiratory Tract Infections (ARI), Toddlers